The word in a dialogically agitated and tension filled world a Bakhtinian reading of 1 Corinthians 1 and 2 - Murtagh, Carmel (2011)
Mikhail Bakhtin offers an understanding of dialogic truth in which meaning is born at the point of contact among various consciousnesses. With the help of contemporary voices in front of the text, this study draws attention to the voices in or behind the text of 1 Corinthians 1 and 2. This is done with a view to showing that Paul is engaging in dialogue and not simply trying to impose a truth on the Corinthians. This view is supported by an examination of the re-accentuation of images such as o` stauro,j( o` lo,goj and h` sofi,a Reading from a dialogical perspective allows for a multiplicity of meanings yet, unlike deconstructionism, does not result in no meaning. The reaccentuation of images explored in this reading reveal a God whose wisdom is revealed in the paradox of the cross; a God who is known in ways that do not necessarily make sense in terms of what is popularly claimed; a God who is revealed in everyday religious, cultural, political, economic and inter-personal tensions.
In Michail Bachtins Verständnis von dialogischer Wahrheit entsteht die Bedeutung durch die Wechselwirkung unterschiedlicher Bewusstseinsebenen. Mit Hilfe von zeitgenössischen Stimmen, die im Text von 1 Korinther 1 und 2 vordergründig erkennbar sind, versucht diese Untersuchung den Blick auf die Stimmen im und hinter dem Text zu lenken. Dadurch soll gezeigt werden, dass Paulus sich hier auf einen Dialog einlässt, und nicht einfach versucht, den Korinthern eine Wahrheit aufzunötigen. Diese Sichtweise wird zudem unterstützt durch eine nähere Untersuchung der Neuakzentuierung von Bildern wie o` stauro,j( o` lo,goj and h` sofi,a. Ein solcher Textzugang aus dialogischer Perspektive lässt Raum für eine Vielzahl von Bedeutungen, aber im Gegensatz zum Dekonstruktivismus resultiert er nicht im völligen Verlust der Bedeutung. Die Neuakzentuierung von Bildern, die durch einen solchen Textzugang erschlossen wird, bringt einen Gott zum Vorschein, dessen Weisheit im Paradox des Kreuzes offenbar wird; einen Gott, der erkennbar wird auf eine Weise, die, gemessen an üblichen Kategorien, nicht unbedingt Sinn ergibt; einen Gott, der sich inmitten von alltäglichen religiösen, kulturellen, politischen, ökonomischen und zwischenmenschlichen Spannungen offenbart.
Keywords: Bachtin, Michail Michajlovič -- 1895-1975; Bibel; Bibel; Texttheorie